DIAGNOSTIC PITFALLS OF BRAIN METASTASES AFTER BRAIN IRRADIATION - Nikolay A. Peev; Svetoslav K. Kalevski; Dimiter G. Haritonov (Peytchinski Publishing, 2010)
Although brain metastases are one of the most frequently diagnosed sequelae of systemic malignancy, their optimal management still is not well defined. In that respect the different diagnostic and therapeutic approaches of BMs patients is an issue for serious discussions. Among the most commonly used diagnostic tools are computed tomography (CT) scans, magnetic resonance imaging (MRI) scans, single photon emission computed tomography (SPECT) and positron emission tomography (PET) scans etc. Nowadays the aforementioned diagnostic modalities are usually combined in order to obtain complete diagnostic information important for establishing the optimal treatment. With the present report we try to elaborate on the value of the modern diagnostic tools in differentiating between tumor progressions versus radiation necrosis in irradiated patients with resected brain metastases. Although the present advancement of the modern imaging modalities differentiating between tumor progression versus radiation necrosis is often difficult. Application of the metabolic imaging modalities like SPECT, PET and proton magnetic resonance spectroscopy (1H-MRS) contributes for the diagnose but still pathological specimens remain a gold standard for distinguishing tumor from necrosis, because none of the imaging modalities is possible to reliably differentiate necrosis from progression in 100% of the cases.